IDENTIFIKASI BAKTERI AIR MINUM ISI ULANG DARI DEPOT YANG MENGGUNAKAN SUMBER AIR NON PDAM DI KOTA SAMARINDA - Nur Maulida Aulia; Sudrajat Sudrajat; Eko Kusumawati (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2017)
This aim of the present work is to know the type and the number of contamination in drinking water refill from depot using Non-PDAM water resource in Samarinda City. The sample were obtained from five subdistricts such as North Samarinda, Sambutan, Palaran, Loa Janan Ilir and Samarinda Ilir. Identification of bacteria using PCA (Plate Count Agar) media, BA (Blood Agar) and MCA (Mac Conkey Agar). Potentially pathogenic colonies tested for biochemical include SIM (Sulfid Indol Motile), SC (Simon Citrate), MR (Methyl red), VP (Voges Proskauer), TSIA (Triple Sugar Iron Agar), Nitrate, Urea, PAA (Phenyl Alanin Agar) and Glucose of. The results show that there is bacterial contamination in drinking water refill from depot using Non-PDAM water resource such as genus Staphylococcus, Klebsiella and Acinetobacter. The number of bacterial contamination were found at least in samples C1 and C2 from Sambutan, sample D2 from Palaran and the most contamination number was found in sample A1 from North Samarinda.